2009
DOI: 10.1080/14926150903118359
|View full text |Cite
|
Sign up to set email alerts
|

Ininiwi-Kiskānītamowin: A Framework for Long-Term Science Education

Abstract: This article first describes an integration of the theoretical models currently found in the literature that discusses the implementation of science programs in Indigenous contexts. The article then reports on the findings from a two-day conference discussing best practice for incorporating Indigenous knowledge in science education, which involved 50 science teachers, consultants, and administrators from urban, rural, and First Nations communities in Manitoba. Participants read "Ininiwi-Kiskānītamowin," a prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Thomas Zwick and Kenneth Miller (1996) showed that Native American fourth graders in Montana who were taught with an outdoor, 'hands on,' group oriented activity-based curriculum, scored higher on science achievement tests than those students taught with a more traditional textbook-based curriculum with few or no activities. Manitoban educators participating in the SAGE (Securing Aboriginal Goals in Education) Conference in February 2008 also acknowledged that ''approaching science education from a land-based experiential learning approach (where students incorporate science as a living, learning process as a part of their everyday lives) is not only positive for Indigenous learners but for all learners (Sutherland and Henning 2009). ''…”
Section: Collective Strategies Across Indigenous Education Programsmentioning
confidence: 98%
“…Thomas Zwick and Kenneth Miller (1996) showed that Native American fourth graders in Montana who were taught with an outdoor, 'hands on,' group oriented activity-based curriculum, scored higher on science achievement tests than those students taught with a more traditional textbook-based curriculum with few or no activities. Manitoban educators participating in the SAGE (Securing Aboriginal Goals in Education) Conference in February 2008 also acknowledged that ''approaching science education from a land-based experiential learning approach (where students incorporate science as a living, learning process as a part of their everyday lives) is not only positive for Indigenous learners but for all learners (Sutherland and Henning 2009). ''…”
Section: Collective Strategies Across Indigenous Education Programsmentioning
confidence: 98%
“…Sutherland and Henning (2009) carried out a literature analysis study in Manitoba and then an interactive action-research project with 50 cross-cultural science educators from schools. Sutherland and Hemming's literature analysis led to four components to successful programs: Downloaded by [University of Otago] at 06:54 27 December 2014 C1.…”
Section: Cross-cultural School Sciencementioning
confidence: 99%
“…In fact, Johnson (2011) described how CRP "is complimentary to components of effective science instruction outlined in the National Science Education Standards" (p. 172; see also Boutte et al, 2010). Culturally relevant science teaching has been engaged successfully with Hispanic students in low-performing urban schools (Johnson, 2011); urban, rural, and First Nations communities in Manitoba (Sutherland & Henning, 2009); African American students (Ares, 2011;Barton, 2003;Boutte et al, 2010); Caribbean immigrants in the northeast United States (Basu, 2010); science teacher education and in-service teachers (Goldston & Nichols, 2009;Kanter & Konstantopoulos, 2010); and rural Filipino students (Handa & Tippins, 2011).…”
Section: Review Of Literaturementioning
confidence: 99%